2013
DOI: 10.1597/12-104
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Occupational Exposure to Polycyclic Aromatic Hydrocarbons and Risk of Oral Cleft-Affected Pregnancies

Abstract: Objective Evaluate whether there is an association between maternal occupational exposure to polycyclic aromatic hydrocarbons (PAHs) and oral cleftsin offspring. This is the first human study of PAHs and clefts of which the authors are aware. Design Case-control study. Setting, Participants Data for 1997–2002 from the National Birth Defects Prevention Study, a large population-based case-control study in the US, were analyzed. Maternal telephone interviews yielded information on jobs held in the month befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 54 publications
2
32
0
Order By: Relevance
“…Consistent with previous studies, a low family income [14], not attending premarital medical examinations [35], family history [1416], maternal occupational hazards exposure [21, 22] and paternal occupational hazards exposure [23] selected as predictors were significantly associated with NSCL/P. According to Krapels et al who examined maternal nutritional factors related to orofacial cleft in Netherlands, increasing intake of vegetable protein can decrease the risk of orofacial cleft [36].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent with previous studies, a low family income [14], not attending premarital medical examinations [35], family history [1416], maternal occupational hazards exposure [21, 22] and paternal occupational hazards exposure [23] selected as predictors were significantly associated with NSCL/P. According to Krapels et al who examined maternal nutritional factors related to orofacial cleft in Netherlands, increasing intake of vegetable protein can decrease the risk of orofacial cleft [36].…”
Section: Discussionsupporting
confidence: 87%
“…Recently, most studies have focused on the identification of risk factors of NSCL/P. Many epidemiological studies have confirmed that maternal age [1012], maternal educational level [2, 13], family income [13, 14], abnormal reproductive histories [15], family history [1416], history of infection during pregnancy [17], medication use during pregnancy [18, 19], ambient environment pollution [20], parental occupational hazards exposure [2123], maternal nutrient intake [2326], and maternal lifestyle factors (alcohol drinking, smoking) [2729] are associated with NSCL/P. However, an individual risk prediction tool for NSCL/P has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Lupo et al (2012) indicated an association between occupational exposure to PAHs among mothers who are over 20 years and occurrence of gastroschisis. Langlois et al (2013) found a statistically significant relationship between maternal occupational exposure to PAHs for cleft lip with or without cleft palate (P trend = 0.02). According to experimental model systems, exposure to PAHs was expected to result in congenital heart defects (CHDs).…”
Section: Teratogenicitymentioning
confidence: 90%
“…Although prior research has quantified levels of exposure and subsequent potential health implications of PAHs in many occupational settings (Bosetti, Boffetta, and La Vecchia 2007; Langlois et al 2013; Lupo et al 2012; O’Brien et al 2016), more information is needed to quantify domestic exposures and their potential health impacts (DellaVale et al 2016; Deziel et al 2014; Kang et al 2015; Kim, Jahan, Kabir, and Brown 2013; Kuo, Hsu, and Lee 2003). Settled dust and particulate matter within homes can be an important exposure route for individuals, in general, and children, in particular.…”
Section: Introductionmentioning
confidence: 99%
“…Intrauterine exposure to high concentrations of PAHs has also been linked to physical impairments, impaired fetal growth (Choi et al 2012; Jedrychowski et al 2017), and congenital malformations such as gastroschisis (Lupo et al 2012), craniosynostosis (O’Brien et al 2016), oral clefts (Langlois et al 2013), and neural tube defects (Ren et al 2011). Lasting health effects have been reported in children after fetal PAH exposure, including decreased height growth (Jedrychowski et al 2015) and childhood obesity (Rundle et al 2012).…”
Section: Introductionmentioning
confidence: 99%